Afatinib inhibits proliferation and invasion and promotes apoptosis of the T24 bladder cancer cell line - TANG, YUNHUA (Exp Ther Med, 2015)
Afatinib is a highly selective, irreversible inhibitor of the epidermal growth factor receptor (EGFR) and human EGFR 2 (HER-2). Although preclinical and clinical studies have indicated that afatinib has antitumor activity and clinical efficacy in non-small cell lung carcinoma, head and neck squamous cell carcinoma and breast cancer, there are few studies investigating its inhibitory effect on human bladder carcinoma cells. In this study, the antitumor effect of afatinib was investigated on the T24 bladder cancer cell line. The T24 bladder cancer cell line was treated with afatinib at various concentrations (0, 1, 5, 10 and 20 µmol/l). MTT assay was used to estimate the proliferation of the T24 cells; flow cytometric analysis was used to estimate the effect of afatinib on T24 cell apoptosis; cell invasion ability was assessed by a Transwell invasion assay; and western blot analysis was used to detect the expression of Bcl-2, Bax, Akt, extracellular-signal-regulated kinase (ERK)1/2, matrix metalloproteinase (MMP)-2 and MMP-9. The MTT assay demonstrated that afatinib inhibited the proliferation of T24 cells in a dose- and time-dependent manner. Flow cytometric analysis revealed that the cell apoptosis rate increased as the concentration of afatinib increased. The cell invasion assay indicated that afatinib treatment significantly inhibited the invasive behavior of T24 cells in a dose-dependent manner. Western blot analysis showed that with increasing afatinib concentrations, Bcl-2, phosphorylated (p)-ERK1/2, p-Akt, MMP-2 and MMP-9 expression levels were significantly decreased, whereas total (t)-ERK1/2 and t-Akt expression levels remained basically unchanged, and Bax expression levels were greatly increased. The results indicate that afatinib inhibits the proliferation and invasion of T24 cells in vitro and induces the apoptosis of these cells by inhibiting the EGFR signaling network.